EXPERIMENTAL PRESERVATION OF SARDINES (SARDINELLA LONGICEPS),USING CHLORTETRACYCLINE. - SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2016)
Effects of dips in 10 and 50 ppm Chlortetracycline solutionon the storage-life of sardines in ice have been studied.5 ppm-CTC-ice in conjunction with dip in 10 ppm CTC-solutionhas also been tried. CTC-treatment considerably reducedbacterial number and gave a better appearance to the fish.The high fat content in sardines resulted in rapid developmentof rancidity. CTC has been found to have no control on thedevelopment of rancidity. Hence, CTC treatment of sardinesis found to be of limited advantage in extending the storage-life of the fish in ice.